Endophytic microbial diversity in coffee cherries of Coffea arabica from southeastern Brazil - Oliveira, Marcelo N. V.; Santos, Thiago M. A.; Vale, Helson M. M.; Delvaux, Júlio C.; Cordero, Alexander P.; Ferreira, Alessandra B.; Miguel, Paulo S. B.; Tótola, Marcos R.; Costa, Maurício D.; Moraes, Célia A.; Moraes, Célia A. (Canadian Journal of Microbiology, 2013)
The microbiota associated with coffee plants may play a critical role in the final expression of coffee quality. However, the microbial diversity in coffee cherries is still poorly characterized. Here, we investigated the endophytic diversity in cherries of Coffea arabica by using culture-independent approaches to identify the associated microbes, ultimately to better understand their ecology and potential role in determining coffee quality. Group-specific 16S rRNA and 26S rRNA genes polymerase chain reaction – denaturing gradient gel electrophoresis and clone library sequencing showed that the endophytic community is composed of members of the 3 domains of life. Bacterial sequences showing high similarity with cultured and uncultured bacteria belonged to the Betaproteobacteria, Gammaproteobacteria, and Firmicutes phyla. Phylogenetic analyses of cloned sequences from Firmicutes revealed that most sequences fell into 3 major genera: Bacillus, Staphylococcus, and Paenibacillus. Archaeal sequences revealed the presence of operational taxonomic units belonging to Euryarchaeota and Crenarchaeota phyla. Sequences from endophytic yeast were not recovered, but various distinct sequences showing high identity with filamentous fungi were found. There was no obvious correlation between the microbial composition and cultivar or geographic location of the coffee plant. To the best of our knowledge, this is the first report demonstrating internal tissue colonization of plant fruits by members of the Archaea domain. The finding of archaeal small-subunit rRNA in coffee cherries, although not sufficient to indicate their role as active endophytes, certainly expands our perspectives toward considering members of this domain as potential endophytic microbes.
Keywords: Coffee cherries; Endophytes; PCR–DGGE; rRNA libraries